Mineralization ratios of nitrogen and phosphorus from decomposing litter in temperate versus tropical forests. Issue 3 (23rd December 2015) - Marklein, Alison R.; Winbourne, Joy B.; Enders, Sara K.; Gonzalez, David J. X.; van Huysen, Tiff L.; Izquierdo, Jorge E.; Light, Derrick R.; Liptzin, Daniel; Miller, Kimberley E.; Morford, Scott L.; Norton, Robert A.; Houlton, Benjamin Z.
Abstract: Aim: Terrestrial ecosystems sequester about 25% of anthropogenic CO2 emissions annually; however, nitrogen (N) and phosphorus (P) limitation of plant productivity and microbial functioning could curtail this key ecosystem service in the future. Our aim is to address variations in nutrient resupply during decomposition – especially whether the N:P ratio of nutrient recycling via mineralization varies within and across diverse forest biomes. Location: Global forest ecosystems. Methods: We compiled data on in situ litter decomposition experiments (leaf, wood and root) from the primary literature to examine the relationships between net N and P mineralization across temperate versus tropical forests world‐wide. We define net nutrient mineralization ratios as the average N:P released from decomposing substrates at a given ecosystem site. Results: We show that net N and P mineralization are strongly correlated within biomes, suggesting strong coupling between N and P recycling in forest ecosystems. The net N:P of leaf‐litter mineralization is higher in tropical forests than in temperate forests, consistent with latitudinal patterns in foliar and leaf‐litter N:P. At the global scale, the N:P of net mineralization tracks, but tends to be lower than that of litter N:P, pointing to preferential P (versus N) mineralization in forest ecosystems. Main conclusions: Our results do not support the view that there is a single, globally consistent mineralization N:P ratio. Instead, our results show that the N:P of net mineralization can be predicted by the N:P of litter, offering a method for incorporating P into global‐scale models of carbon–nutrient–climate interactions. In addition, these results imply that P is scarce relative to microbial decomposer demands in tropical forests, whereas N and P may be more co‐limiting when compared with microbial biomass in the temperate zone.